Variação entre os pronomes tu e você na função de sujeito na fala de Natal (RN): uma abordagem sociofuncionalista - Silva, Francielly Coelho da (2015)
In this dissertation, under the light of a sociofunctionalist approach (TAVARES, 2003; 2013; GORSKI; TAVARES, 2013), I analyze 378 data of pronouns tu and você extracted from 12 conversations belonging to Natal Conversational Data Base (CUNHA, 2010). I have the following objectives: (i) mapping linguistic and extralinguistic specialization trends of second person singular subject pronouns tu and você in the speech of Natal (RN); (ii) assessing the role of the principle of persistence (HOPPER, 1991) as a possible motivating factor of specialization trends of pronouns tu and você; (iii) identify in which of the six pronouns subsystems proposed by Scherre et al. (2009) is situated the speech community of Natal portrayed in this study. In order to achieve the proposed objectives, I submitted the data to multivariate statistical analysis, which have provided frequencies and relative weights.I obtained, as relevant factor groups, according to the statistical analysis, the nature of the relationship between the interlocutors (if the relationship is asymmetric, less intimate, and more formal, the use of você is favored; if the relationship is symmetrical, intimate and informal, the use of tu is favored); the degree of formality of the environment in which the conversation takes place (in more informal environments tu was favored; in more formal environments você were favored); and the type of discourse (reported / not reported) (tu was favored in not reported discourse and você was favored in reported discourse). Based on results regarding to these factors groups, I organized a panorama of specializations of pronouns tu and você, noting that tu seems specialized for more informal contexts of use than those for which você seems specialized. The motivation underlying these trends of specialization may be the principle of persistence, since along its historical development, você carries a trace of greater formality or, at least, less intimacy, when contrasted to tu. Finally, I concluded that, of the six pronoun subsystems proposed by Scherre et al. (2009), the speech community of Natal can be framed in the fifth, characterized by variable use of subject pronouns tu and você, with more frequent use of você than tu, and rare occurrence of agreement of tu with second-person singular verb.